Cell phone dependence, habits and attitudes towards reading and its relationship with academic performance - A. Hilt, Jorge (2019)
Cell phone (mobile) has become part of the daily life of young people and its use continues to expand, being used every time at a younger age. At the same time, the use of the cell phone can become a distraction when it is used too much for entertainment purposes, especially when it competes with the time that should be spent on reading and doing homework. Therefore, this study tried to establish whether there was a relationship between cell phone use, habits and attitudes towards reading and its influence on academic performance in middle-level students of the Mariano Moreno Adventist Institute, in the city of Posadas, Misiones (Argentina), in the school year 2018. The study was cross-sectional, correlational and quantitative. To measure the use of the cell phone, the Mobile Dependency Test (TDM) was used; Attitudes and habits towards reading were valued with the HAL questionnaire, and academic performance was obtained by means of the first quarter qualification of the 2018 school year. The sample consisted of 126 students from first to fifth year, representing 66.67 % of middle-level students. We found evidence that there is a negative relationship between cell phone dependence and the other study variables: (a) reading habits, (b) attitudes towards reading and (c) academic performance. Regarding gender, the group of students obtained higher scores in all the variables of the study. Although women make greater use of cell phones and have a greater perception of dependence, this does not prevent them from obtaining better grades than men. Almost half of the sample uses Instagram as the preferred social network.